2011
DOI: 10.1007/s00267-011-9730-4
|View full text |Cite
|
Sign up to set email alerts
|

Large Woody Debris Input and Its Influence on Channel Structure in Agricultural Lands of Southeast Brazil

Abstract: Riparian forests are important for the structure and functioning of stream ecosystems, providing structural components such as large woody debris (LWD). Changes in these forests will cause modifications in the LWD input to streams, affecting their structure. In order to assess the influence of riparian forests changes in LWD supply, 15 catchments (third and fourth order) with riparian forests at different conservation levels were selected for sampling. In each catchment we quantified the abundance, volume and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 51 publications
2
27
1
6
Order By: Relevance
“…This is not which occurs in the study area, where the landscape is degraded and remnant forests are highly fragmented (Valente and Vettorazzi, 2008;Paula et al, 2011). Neill et al (2001) found higher concentrations of nitrate in forested catchments than in pasture ones in Amazon streams, and also, the use of fertilizers in sugarcane plantations in Brazil is lower compared to other more developed countries (Martinelli and Filoso, 2008).…”
Section: Management Implicationsmentioning
confidence: 73%
See 1 more Smart Citation
“…This is not which occurs in the study area, where the landscape is degraded and remnant forests are highly fragmented (Valente and Vettorazzi, 2008;Paula et al, 2011). Neill et al (2001) found higher concentrations of nitrate in forested catchments than in pasture ones in Amazon streams, and also, the use of fertilizers in sugarcane plantations in Brazil is lower compared to other more developed countries (Martinelli and Filoso, 2008).…”
Section: Management Implicationsmentioning
confidence: 73%
“…Maps of land use, hydrography and catchment limits were obtained from Paula et al (2011) using topographic maps (1:10 000, year 1979, Cartographic and Geographic Institute of the State of Sa˜o Paulo) and aerial photographs (scale 1:30 000, year 2000). Maps were derived using the software ArcGIS 9.2.…”
Section: Landscape Characteristics Of the Catchmentsmentioning
confidence: 99%
“…Conservation strategies for aquatic biodiversity in these systems should seek to restore and conserve riparian and landscape diversity (but see a context dependence evaluation by Nislow 2005). Through this way, it is possible to protect instream habitats from siltation (Sweeney and Newbold 2014), provide woody debris for instream habitat (Paula et al 2011(Paula et al , 2013, and mitigate the proliferation of grass on stream banks (Bunn et al 1997). This last goal is the main factor associated with functional redundancy in the studied region.…”
Section: Discussionmentioning
confidence: 98%
“…Indiretamente, esses efeitos determinam impactos negativos sobre a estrutura física e química do habitat dos peixes. Estes e outros aspectos foram estudados em trabalhos recentes, como Buss et al (2002), Allan (2004), Ferreira e Casatti (2006), Casatti (2010), De Paula et al (2011), Machado et al (2011.…”
Section: Introductionunclassified